Virus-vector relationship in the Citrus leprosis pathosystem - Tassi, Aline Daniele (2017)
Citrus leprosis has been one of the most destructive diseases of citrus in the Americas. In the last decade important progress has been achieved such as the complete genome sequencing of its main causal agent, Citrus leprosis virus C (CiLV-C), belonging to a new genus Cilevirus. It is transmitted by Brevipalpus yothersi Baker (Acari: Tenuipalpidae), and is characterized by the localized symptoms it induces on the leaves, fruits and stems. It occurs in the American continents from Mexico to Argentina. The virus was until recently considered restricted to Citrus spp. However, it was found naturally infecting other plants species as Swinglea glutinosa Merrill and Commelina benghalensis L., and has been experimentally transmitted by B. yothersi to a large number of plant species. Despite these advances little is known about the virus-vector relationship that is a key to understanding the epidemiology of the disease. Some components of the CiLV-C/B. yothersi relationship were determined using the common bean (Phaseolus vulgaris L. cv. ‘IAC Una’) as a test plant. They included: (a) the virus acquisition access period was 4 h; (b) the virus inoculation access period was 2 h; (c) the latent period between acquisition and inoculation was 7 h; (d) the period of retention of the virus by a single viruliferous mite was at least 12 days; (d) the percentage of viruliferous individuals from mite colonies on infected tissues ranged from 25 to 60%. The experiments confirmed previous data that all developmental stages of B. yothersi (larva, protonymph and deutonymph, adult female and male) were able to transmit CiLV-C and that transovarial transmission of the virus did not occur. CiLV-C can be acquired from lesions on leaves, fruits and stems by B. yothersi. Based on the distribution of lesions produced by single viruliferous B. yothersi on bean leaves, it is concluded that they tend to feed in restricted areas, usually near the veins. The short latent and transmission periods during the larval stage suggest that the CiLV-C/B. yothersi relationship is of the persistent circulative type.